2012
DOI: 10.3389/fpsyg.2012.00537
|View full text |Cite
|
Sign up to set email alerts
|

Eyes on the Mind: Investigating the Influence of Gaze Dynamics on the Perception of Others in Real-Time Social Interaction

Abstract: Social gaze provides a window into the interests and intentions of others and allows us to actively point out our own. It enables us to engage in triadic interactions involving human actors and physical objects and to build an indispensable basis for coordinated action and collaborative efforts. The object-related aspect of gaze in combination with the fact that any motor act of looking encompasses both input and output of the minds involved makes this non-verbal cue system particularly interesting for researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 60 publications
5
84
1
2
Order By: Relevance
“…The TGE is a passive observation task that evaluates gaze regulation in social interaction. The task introduces emotional verbal and nonverbal content and examines the participant's nonverbal interaction using gaze direction (Pfeiffer et al., ). Participants in the TGE engaged in triadic interactions involving unfamiliar human agents and nonhuman stimuli.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TGE is a passive observation task that evaluates gaze regulation in social interaction. The task introduces emotional verbal and nonverbal content and examines the participant's nonverbal interaction using gaze direction (Pfeiffer et al., ). Participants in the TGE engaged in triadic interactions involving unfamiliar human agents and nonhuman stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…The TGE is a passive observation task that evaluates gaze regulation in social interaction. The task introduces emotional verbal and nonverbal content and examines the participant's nonverbal interaction using gaze direction (Pfeiffer et al, 2012). Participants in the TGE engaged in triadic interactions During the social blocks, participants observed two social video clips, each with two interacting agents who take turns expressing one of four affective narratives (neutral/angry/ happy/sad) while alternating their gaze spontaneously between the other agent and the participant.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, in the present study, virtual characters lacked any verbal or facial information. In particular, information about eye-movements and gaze direction is informative to person perception in general [Georgescu et al, 2013;Kuzmanovic et al, 2009;Pfeiffer et al, 2012] and power perception in particular [Dovidio & Ellyson, 1982;Dunbar & Burgoon, 2005]. For instance, there are findings showing the importance of visual dominance behavior, implying that less dominant people look less directly to interactants while speaking than while listening [Dovidio & Ellyson, 1982].…”
Section: Discussionmentioning
confidence: 99%
“…Knoeferle and Kreysa (2012) found that listeners rapidly respond to shifts in speaker's gaze in affecting not only their allocation of visual attention, but also their processing of syntactic structures and assignment of thematic roles, even when such information is not central to the task. Additionally, Pfeiffer and colleagues (Pfeiffer et al, 2012) used a novel interactive eye-tracking paradigm to show that both congruency and latency of an interaction partner's gaze behavior influence one's experience of agency, and that shared attention takes longer to establish than joint attention.…”
mentioning
confidence: 99%